Muscle activity during the incline shoulder press in relation to the exercise intensity - Stronska, K.; Bojacz, P.; Golas, A.; Maszczyk, A.; Zajac, A.; Stastny, P. (Acta Gymnica, 2018)
Background: The incline machine shoulder press (IMSP) is an alternative resistance exercise to the bench press associated with throwing performance. The muscle activity during IMSP has not yet been described in females and at different exercises intensities.